Effect of scape regulation on seed yield and quality in onion (Allium cepa) - R, YALAMALLE V; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2019)
Flowering plants often produce less seed than the number of flowers they produced. A field experiment was conducted to study the effect of the scape regulation on seed yield and quality in onion (Allium cepa L.) cv. Pusa Ridhi during rabi 2015-16 and 2016-17, at Unit of Vegetable Research and Demonstration Unit (UVRDC), ICARIndian Agricultural Research Institute, New Delhi. Onion plants producing six scapes/plant were selected and the scape numbers were regulated from 1-6/plant. The results from the present experiment reveal that, scape regulation significantly influences the seed quality. The scape length, umbel diameter was significantly higher by 13.36% and 25.65% respectively, in plants up to three scapes/plant, in comparison to plants with six scapes/plant. Highest number of florets/flower was found in plants with one scape/plant, which was 50.47% higher than the plants with six scape/plant. Plants with single scape produced 88.78% more seed yield/umbel in comparison to plants with six scapes/plant. Seed quality parameters like 1000-seed weight, speed of germination, seedling vigour were higher in plants up to four scapes/plant. Though there was reduction in the overall yield but the reduced yield is likely to be compensated by high seed vigour which may lead to higher filed emergence. It is suggested that during seed production of onion maximum of four scapes may be retained to obtain seeds with high quality.